Knowledge and provision of misoprostol among pharmacy workers in Senegal: a cross sectional study - Kate Reiss; Katharine Footman; Eva Burke; Nafissatou Diop; Ramatoulaye Ndao; Babacar Mane; Maaike van Min; Thoai D. Ngo (BMC, 2017)
Abstract Background Making misoprostol widely available for management of postpartum haemorrhage (PPH) and post abortion care (PAC) is essential for reducing maternal mortality. Private pharmacies (thereafter called "pharmacies") are integral in supplying medications to the general public in Senegal. In the case of misoprostol, pharmacies are also the main supplier to public providers and therefore have a key role in increasing its availability. This study seeks to understand knowledge and provision of misoprostol among pharmacy workers in Dakar, Senegal. Methods A cross-sectional survey was conducted in Dakar, Senegal. 110 pharmacy workers were interviewed face-to-face to collect information on their knowledge and practice relating to the provision of misoprostol. Results There are low levels of knowledge about misoprostol uses, registration status, treatment regimens and side effects among pharmacy workers, and corresponding low levels of training on its uses for reproductive health. Provision of misoprostol was low; of the 72% (n = 79) of pharmacy workers who had heard of the product, 35% (n = 27) reported selling it, though rarely for reproductive health indications. Almost half (49%, n = 25) of the respondents who did not sell misoprostol expressed willingness to do so. The main reasons pharmacy workers gave for not selling the product included stock outs (due to product unavailability from the supplier), perceived lack of demand and unwillingness to stock an abortifacient. Conclusions Knowledge and availability of misoprostol in pharmacies in Senegal is low, posing potential challenges for delivery of post-abortion care and obstetric care. Training is required to address low levels of knowledge of misoprostol registration and uses among pharmacy workers. Barriers that prevent pharmacy workers from stocking misoprostol, including weaknesses in the supply chain and stigmatisation of the product must be addressed. Low reported sales for reproductive health indications also suggest limited prescribing of the product by health providers. Further research is needed to explore the reasons for this barrier to misoprostol availability.